2020
DOI: 10.1038/s41598-020-74596-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-related differences in homocysteine concentration: a cross-sectional study of the general population of China

Abstract: The primary goals of this study were to evaluate the gender- and age-related differences in homocysteine concentration in the general population of China and possible influencing factors. A total of 7872 subjects, divided into male and female groups, participated in this retrospective study. The average homocysteine level, prevalence of hyperhomocysteinemia, and independent factors affecting homocysteine concentration were analyzed. The homocysteine level was significantly higher in males than in females in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 43 publications
7
51
3
Order By: Relevance
“…Interestingly, we found that Hcy levels were negatively associated with SoP score, but not score for other cognitive domains, in patients with schizophrenia aged 18-29 years after adjustment for age, BMI, and education. Additionally, with increasing age, no relationship was observed between these factors, in contrast most previous studies [28][29][30] . The inconsistent results may be because plasma Hcy levels result from a complex process mediated by the interaction between genetic and environmental factors, and the independent factors associated with Hcy levels and cognitive de cits differed according to age 31 .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Interestingly, we found that Hcy levels were negatively associated with SoP score, but not score for other cognitive domains, in patients with schizophrenia aged 18-29 years after adjustment for age, BMI, and education. Additionally, with increasing age, no relationship was observed between these factors, in contrast most previous studies [28][29][30] . The inconsistent results may be because plasma Hcy levels result from a complex process mediated by the interaction between genetic and environmental factors, and the independent factors associated with Hcy levels and cognitive de cits differed according to age 31 .…”
Section: Discussioncontrasting
confidence: 98%
“…In several longitudinal studies, the progression of changes in Hcy levels associated with age was not con rmed. Additionally, a recent large-sample study including 7872 subjects evaluated the age-related differences in Hcy levels in a general Chinese population and showed that the Hcy levels rst decreased, then increased, and signi cantly increased after 50 years of age 17 , similar to the results of our study. However, some previous studies did not observe a statistically signi cant association between Hcy levels and age 18 , whereas other studies reported that plasma Hcy levels increased signi cantly with age in the general population and patients with schizophrenia 19 ; 20 .…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, the PTZ-induced sexual dimorphism in the brain methionine level also deserves attention, as methionine is a precursor of a pro-convulsant homocysteine [ 41 ]. Homocysteine levels are higher in the plasma of males compared to females [ 42 ], but their increase is more dangerous to the female brain than the male brain [ 43 ]. In the animals without exposure to PTZ, there is no difference in the brain methionine level between the males and females ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tumor necrosis factor alpha (TNF-α) has been reported to be increased in a stepwise manner, with centenarians displaying greater concentrations than 80-year-olds, who in turn display greater concentrations than younger individuals ( Franceschi et al, 2007 ). Similarly, homocysteine is greater in those aged over 50years of age compared to younger individuals and is associated with unhealthy lifestyle habits, such as smoking ( Xu et al, 2020 ). Moreover, IL-6 is greater in advanced age ( Bruunsgaard et al, 1999 ; Baylis et al, 2013 ), while intracellular pro-inflammatory cytokines, such as interferon gamma (IFN-γ) and TNF-α, are greater in older participants’ T cells than younger counterparts’ T cells ( Zanni et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%